Expanding the genotypic spectrum of Jalili syndrome: Novel CNNM4 variants and uniparental isodisomy in a north American patient cohort. Issue 3 (5th February 2020) - Prasov, Lev; Ullah, Ehsan; Turriff, Amy E.; Warner, Blake M.; Conley, Julie; Mark, Paul R.; Hufnagel, Robert B.; Huryn, Laryssa A.
Abstract: Jalili syndrome is a rare multisystem disorder with the most prominent features consisting of cone‐rod dystrophy and amelogenesis imperfecta. Few cases have been reported in the Americas. Here we describe a case series of patients with Jalili syndrome examined at the National Eye Institute's Ophthalmic Genetics clinic between 2016 and 2018. Three unrelated sporadic cases were systematically evaluated for ocular phenotype and determined to have cone‐rod dystrophy with bull's eye maculopathy, photophobia, and nystagmus. All patients had amelogenesis imperfecta. Two of these patients had Guatemalan ancestry and the same novel homozygous CNNM4 variant (p.Arg236Trp c.706C > T) without evidence of consanguinity. This variant met likely pathogenic criteria by the American College of Medical Genetics guidelines. An additional patient had a homozygous deleterious variant in CNNM4 (c.279delC p.Phe93Leufs*31), which resulted from paternal uniparental isodisomy for chromosome 2p22‐2q37. This individual had additional syndromic features including developmental delay and spastic diplegia, likely related to mutations at other loci. Our work highlights the genotypic variability of Jalili syndrome and expands the genotypic spectrum of this condition by describing the first series of patients seen in the United States.